IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG HAK TENAGA KERJA WANITA DI ALFAMART DAN INDOMARET DI KOTA PEKANBARU - Gita Prina; Zahirman Zahirman; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : this research background in the background by the large number of problems Still associated with employment in the city of Pekanbaru in particular labor women. The visible phenomena related to the employment problem of these women, among other things: the amount of labour women are increasing each year, there are still large number of women employed in the evening, still the number of rights the rights of these women's labor not given such rights to breastfeed the baby, menstrual leave, etc. So the author would like to see how the employment rights of women, and alfamart indomaret in pekanbaru. This descriptive qualitative research methods. The used instrument that is now composed of 15 questions about the law regarding the rights of female labor. The data were analyzed using the formula P = f/Nx100% to find out the percentage of answers from the respondents. The calculation of the percentage of overall respondents answer obtained answers